Analysis of Changes in Trade in Developed Land Property in Poland between 2017 and 2020 - Hajduga, Piotr (Analiza zmian w obrocie zabudowanymi nieruchomościami gruntowymi w Polsce w latach 2017-2020, 2023)
In contemporary socio-economic reality, there are many elements, both material and non-material, that play a significant role in shaping it. Treating economics as a science that studies people’s behaviour in producing, distributing, and consuming goods and services, then undoubtedly, one of the most critical elements shaping this process is real estate, which cannot be overestimated in market processes. From the beginning of the formation of the market economy, real estate was at its very centre and determined directly and indirectly the direction of development of this economy. This author focused on identifying changes taking place in the trade in developed land properties on the Polish real estate market in terms of its forms. The research procedure used methods of literature criticism and descriptive statistics.
Biblioteka Regionalisty = Regional Journal, 2023, Nr 23, s. 22-31
Keywords: real estate; forms of real estate trading; sales volume; sales value; nieruchomość; formy obrotu nieruchomościami; wielkość sprzedaży; wartość sprzedaży